THE EFFECT OF PRODUCTIVE CAPACITIES ON MINING INDUSTRY OF KAZAKHSTAN - Koyanbayeva, Zhuldyz (Nazarbayev University School of Mining and Geosciences, 2024)
The thesis examines the relationship between Productive Capacities and mineral output in Kazakhstan, a country noted for its richness in a variety of mineral resources. As the demand for minerals continues to rise, it has been of particular interest to develop new mining sites. The abundance of deposits around the world has created competition among extractive countries, with the mineral potential becoming not the only decisive factor in investment decisions. The study identifies productive capacities that influence the mining output, hence, increasing the opportunity for further investments and development. The thesis identifies several significant variables in relation to annual mining output in Kazakhstan, including energy, transport, productive capacity index (PCI), private sector, and ICT. The findings underscore the importance of these factors in driving the mining industry’s productivity and output levels. By understanding the impact of these factors, Kazakhstan can potentially attract more mineral investments, develop new mining sites, and boost its economic state and employment rates.
Keywords: Type of access: Restricted